Pemanfaatan Hutan Produksi Desa Balaroa Pewunu Kecamatan Dolo Barat Kabupaten Sigi - I komang Suprianto; Mohammad Zeylo Auriza; Maskuri Sutomo (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
Forests have a production function, namely economic value, such as wood, rattan, agarwood and so on. Forests have an ecological function because forests are very important for the survival of human beings, animals and plants. Ecological functions include absorbing carbon dioxide and then producing oxygen for life, a source of water, preventing erosion and flooding, habitat for animals, and a source of biodiversity. The purpose of planting tree seedlings is a form of making a production forest where it retains water during floods, secondly as an increase in the economy of the people of Balaroa Pewunu Village. The author uses a descriptive observational method using a persuasive approach to the community by interviews and field observations. By planting candlenut, avocado, jackfruit and petai trees. Implementation of tree seed planting activities on holidays, namely Sundays and trees planted around the river area, with the involvement of village government officials and Risma youth. The planting was carried out in stages considering that there were 850 trees planted including: 500 candlenut seeds, 200 avocado seeds, 100 jackfruit seeds, and 50 petai seeds. The target achieved in planting tree seedlings is expected to become community income in the future. From the community service activities it was concluded that the land in the production forest was used by the community for gardening and farming, then utilizing forest products. The types of forest products that are widely used are candlenut, tamarind, jackfruit, guava, and pineapple.